2003
DOI: 10.1074/jbc.m304968200
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Analysis of Platelet-derived Growth Factor Receptor/Phosphoinositide 3-Kinase/Akt Signaling in Fibroblasts

Abstract: Isoforms of the serine-threonine kinase Akt coordinate multiple cell survival pathways in response to stimuli such as platelet-derived growth factor (PDGF). Activation of Akt is a multistep process, which relies on the production of 3 -phosphorylated phosphoinositide (PI) lipids by PI 3-kinases. To quantitatively assess the kinetics of PDGF receptor/PI 3-kinase/Akt signaling in fibroblasts, a systematic study of this pathway was performed, and a mechanistic mathematical model that describes its operation was f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
94
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(110 citation statements)
references
References 65 publications
(54 reference statements)
16
94
0
Order By: Relevance
“…Variable conclusions about population responses to different growth factors have been reached by more traditional endpoint assays, including the use of serial immunoblotting or immunocytochemistry to probe for Akt or substrate phosphorylation (Borisov et al, 2009;Chen et al, 2009;Kubota et al, 2012;Park et al, 2003). Here, by continuous monitoring, we were able to collect a consistent and more robust data set with less experimental effort and fewer assumptions.…”
Section: Advantages Of Live-cell Imaging In Understanding Signaling Pmentioning
confidence: 87%
“…Variable conclusions about population responses to different growth factors have been reached by more traditional endpoint assays, including the use of serial immunoblotting or immunocytochemistry to probe for Akt or substrate phosphorylation (Borisov et al, 2009;Chen et al, 2009;Kubota et al, 2012;Park et al, 2003). Here, by continuous monitoring, we were able to collect a consistent and more robust data set with less experimental effort and fewer assumptions.…”
Section: Advantages Of Live-cell Imaging In Understanding Signaling Pmentioning
confidence: 87%
“…We showed that this is partly due to saturation of Akt-effector phosphorylation, but it remains unclear why saturation occurs. Saturation of the PI3K-Akt pathway has also been reported in other contexts -for instance, in response to high concentrations of certain growth factors (Park et al, 2003) -suggesting that saturation is not Adv-specific. The simplest molecular explanation for saturation in Adv-infected cells is that Akt and its substrates are negatively regulated by different protein phosphatases.…”
Section: Journal Of Cell Science 119 (18)mentioning
confidence: 95%
“…The key network nodes and links include PI3K mediated activation of PKB, activation of Ras and downstream kinases such as ERK and activation of PLCc1 (Park et al, 2003). Several other small GTPases in addition to Ras, such as Rap, Rho and Rac, also participate in responses to PDGF-BB.…”
Section: Fibroblasts Lacking Plce Have Impaired Chemotaxis In Pdgf-bbmentioning
confidence: 99%